Interfacial Development of Electrophoretically Deposited Graphene Oxide Films on Al Alloys. Issue 11 (1st January 2015) - Jin, Sumin; Pham, Viet Hung; Dickerson, James H.; Brochu, Mathieu
Abstract : Sustained adhesion between a film and its substrate is critical for electronic device and coating applications. Interfacial development between electrophoretically deposited graphene oxide films on Al 1100 and Al 5052 alloys were investigated using FT-IR and XPS depth profiling techniques. The results suggest metal ion permeation from the substrates into deposited graphene oxide films. The interface between the films and the substrates were primarily composed of Al-O-C bonds from oxygen-containing defects on graphene oxide plane rather than the expected formation of Al-C bonds. Films were heat treated at 150°C and underwent a partial removal of oxygen-bearing groups. Peak shifts in Al 2p XPS spectra and change in Al ion distribution through out the film suggested change in chemical bond between Al and O upon heat and indicated that Al–O bond is the major influence in forming adhesive bond between the graphene oxide films and the Al alloy substrates.